A Representation of illness in the novel "A Concert of Bach’s music" by Hortensia Papadat-Bengescu - Teodorowicz, Justyna (Balcanica Posnaniensia. Acta et studia, 2021)
The article discusses the problem of illness in the novel A Concert of Bach’s music by Hortensia Papadat-Bengescu, a Romanian interwar writer considered to be a precursor of Romanian psychological prose. Illness, being one of the major themes in her writings, has usually been interpreted as a reflection of Romanian declining society. In the present article, we analyse the most interesting example of a sick character in Hortensia Papadat-Bengescu’s novels, that is prince Maxentiu, who suffers from tuberculosis. We suggest some possible interpretations of his case in the context of contemporary scientific research, especially in the domain of the sociology of illness. We discuss, among others, illness as a biographical disruption, the problem of character’s personal and social identity in chronic illness, as well as his attitude towards death.